INDIRECT MEASUREMENT METHODOLOGY OF CARGO WEIGHT LIFTED BY THE EXCAVATOR IN THE CRANE MODE - M. S. Korytov; I. K. Kanin (Вестник СибАДИ)
Introduction. To solve the indirect measurement problem of the cargo weight lifted by the excavator in crane mode the authors propose the specific method and develop mathematical model according to the indications of hydraulic fluid pressure sensors in the piston and rod cavities of boom lifting cylinders. Moreover, the signals from the angle sensor of the boom and the handle relative to the gravity horizon are used, the roll and pitch sensors of the rotary column of the excavator relative to the gravity horizon are additionally applied.Materials and methods. As initial data of the indirect measurement method of cargo mass, constant design parameters, constant masses of moving links are used, such as booms with handle hydraulic cylinder, handles with bucket hydraulic cylinder and bucket turning mechanism, bucket weight. In addition, constant linear number and angular machine dimensions are included in the investigation. To obtain analytical formulas of the method, the method of homogeneous coordinates is applied, as well as the method of direct analytical inference.Results. The developed design scheme of the method is presented. As a result, the position of the excavator crane is described in the right-hand rectangular coordinate system. Moreover, the technique of indirect measurement of cargo mass according to the indications of hydraulic fluid pressure sensors in the form of formulae linear sequence is presented.Discussion and conclusion. The accuracy of the developed method was estimated by comparison with the results of the full-scale experiment. The relative reduced measurement error in the range of boom angles’ measurement and the crane-excavator handle was less than ten percent. Therefore, the technique merits are its simplicity, as well as record of the roll and pitch angles of the crane-excavator turntable element.